Evaluation of efficacy, expulsion and safety of post-placental and intra-cesarean insertion of intrauterine contraceptive devices - Singh, Swati; Malik, Renu; Ahalawat, Ravinder; Taneja, Bal Krishan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of the study was to evaluate the safety and efficacy of immediate postpartum intrauterine contraceptive device (PPIUCD) insertion in women delivering vaginally or by cesarean section. Methods: This prospective study was carried out at General Hospital [Tertiary care] from August 2014 to September 2015. All antenatal patients admitted for delivery to our hospital were counseled for PPIUCD. Also consent was taken from those who opted for PPIUCD insertion. Results: A total of 2016 women were counseled for PPIUCD adoption. Out of this, 1312 women accepted this method. Total number of deliveries during the study period was 2835. Total acceptance rate was 46.27%. The expulsion rate was 10.63% while removal rate was 7.74%. Out of 555 women who came for follow up, 453 women continued PPIUCD. Thus, continuation rate was 81.62%. Conclusions: PPIUCD is easily accessible, reversible and cost effective contraceptive method for most postpartum women specially lactating women.